Photon number statistics uncover the fluctuations in non-equilibrium lattice dynamics - Esposito, Martina; Titimbo, Kelvin; Zimmermann, Klaus; Giusti, Francesca; Randi, Francesco; Boschetto, Davide; Parmigiani, Fulvio; Floreanini, Roberto; Benatti, Fabio; Fausti, Daniele (Nature Communications, 2015)
Fluctuations of the atomic positions are at the core of a large class of unusual material properties ranging from quantum para-electricity to high temperature superconductivity. Their measurement in solids is the subject of an intense scientific debate focused on seeking a methodology capable of establishing a direct link between the variance of the atomic displacements and experimentally measurable observables. Here we address this issue by means of non-equilibrium optical experiments performed in shot-noise-limited regime. The variance of the time-dependent atomic positions and momenta is directly mapped into the quantum fluctuations of the photon number of the scattered probing light. A fully quantum description of the non-linear interaction between photonic and phononic fields is benchmarked by unveiling the squeezing of thermal phonons in α-quartz.
CRIS-Team Scopus Importer:2022-07-20